Risk factors and clinical characteristics of patients with nosocomial influenza A infection. Issue 8 (19th December 2019) - Naudion, Pauline; Lepiller, Quentin; Bouiller, Kevin
Abstract: Influenza is a public health burden, responsible for more than half a million deaths worldwide each year and explosive outbreaks in‐hospital care units. At present, little is known about clinical characteristics and outcomes with nosocomial influenza infection. To assess clinical characteristics and outcome between nosocomial and community‐acquired (CA) influenza in a tertiary care hospital. A retrospective study of hospitalized patients in a French tertiary care hospital from 1st December 2016 to 28th February 2017 for flu‐illness confirmed by reverse transcription PCR. Overall, 208 patients with laboratory‐confirmed influenza were included; whose 49 nosocomial cases (23.6%). Patients with nosocomial influenza were significantly older (79.1 ± 15.5 vs 64.8 ± 31.1 years old; P  = .003), with the more rapidly fatal disease (10.2% vs 1.3%; P  = .0032). They had a less respiratory failure (8.2% vs 21.4%; P  = .036) but had a longer length of hospitalization (47.3 vs 12.9 days; P  < .001) than patients with CA influenza. During this influenza outbreak, 19 patients died (9.1%), none of them were vaccinated. Effective control of outbreaks in hospital facilities is challenging. Hospitalized patients are vulnerable to nosocomial Influenza infections that can increase the length of stay and be responsible for the death. Surveillance and early warning systems should be encouraged. Vaccination policies in conjunction with isolation measures and better hand hygiene could reduce virus spreading in hospitals. Highlights: In the influenza season 2016‐2017, 49/208 (23.6%) cases were nosocomial influenza infection. Patients with nosocomial influenza were older, fragile and less vaccinated than community acquired influenza. Mortality rate was 16.3% (8/49) in patients with nosocomial influenza and among them none was vaccinated. The mortality rate was not higher in patients with nosocomial influenza than community acquired influenza. But the lengths of stay were longer.